The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1051/0004-6361/201527579
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the history of water ice formation from HDO/H2O and D2O/HDO ratios in protostellar cores

Abstract: Recent interferometer observations have found that the D 2 O/HDO abundance ratio is higher than that of HDO/H 2 O by about one order of magnitude in the vicinity of low-mass protostar NGC 1333-IRAS 2A, where water ice has sublimated. Previous laboratory and theoretical studies show that the D 2 O/HDO ice ratio should be lower than the HDO/H 2 O ice ratio, if HDO and D 2 O ices are formed simultaneously with H 2 O ice. In this work, we propose that the observed feature, D 2 O/HDO > HDO/H 2 O, is a natural conse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
141
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(154 citation statements)
references
References 60 publications
13
141
0
Order By: Relevance
“…Temperature-dependent ideal-gas internal partition functions, Q int (T ), have been determined, in the range of 0 to 6000 K, for the following molecules: ortho-and para-D 2 16 O, set of first-principles energy levels, over three million for each isotopologue, have been utilized during the explicit summation. These ideal-gas internal partition functions and their first two moments were then employed to obtain the following thermochemical functions in the same temperature range: Gibbs energy function, enthalpy, entropy, and isobaric heat capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Temperature-dependent ideal-gas internal partition functions, Q int (T ), have been determined, in the range of 0 to 6000 K, for the following molecules: ortho-and para-D 2 16 O, set of first-principles energy levels, over three million for each isotopologue, have been utilized during the explicit summation. These ideal-gas internal partition functions and their first two moments were then employed to obtain the following thermochemical functions in the same temperature range: Gibbs energy function, enthalpy, entropy, and isobaric heat capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure does not ensure that we have the complete set of rovibrational states very close to the dissociation limit. This minor shortcoming of the present treatment is reflected in the somewhat increased uncertainties at the highest temperatures for D 2 17 O and D 2 18 O (note the large uncertainties employed for energy levels above 35 000 cm −1 , Table 1). …”
Section: First-principles Energy Levelsmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed the D/H ratio in cold dense objects can reach of the order of 0.1 -0.2 compared to the average of 1.5×10 -5 in the galactic interstellar medium 28,29 . Recent studies have reported the degree of deuterium enrichment and fractionation in many stellar objects at different evolutionary stages [30][31][32][33][34][35][36][37][38][39][40][41] . Fontani et al 42 show that surface chemistry has an important role in determining the fractional deuteration of some molecules (e.g.…”
Section: Introductionmentioning
confidence: 99%